Synthetic Medium for Growing Single Cells of Tobacco - E. Noerhadi (Institute for Research and Community Services (LPPM) ITB, 1967)
1. Studies were done to find out a synthetic defined medium for growing single cells of tobacco. Two kinds of media were tried for these purposes. With several changes in components, the revised medium of LINSMAIER & SKOOG (6) seemed to be good lot suspension and plating cultures of tobacco cells. The medium used by ERARLE & TORREY (3) for cells of Convolvulus also gave the desired results (table 1, plate 3).2. Growth of both callus and single cell cultures occurred on comparable kinetin concentrations.3. These studies (about the relationship between IAA and kinetin) gave no evidence of differentiation of the cell colonies within seven weeks after transferring the cells into the medium (plate 5).